Search for Higgs-like bosons decaying into long-lived exotic particles - Aaij, Roel; Adeva, B.; Adinolfi, M.; D'Argent, Philippe; Bachmann, Sebastian; Braun, Svende; Britsch, Markward; Comerma-Montells, Albert; De Cian, Michel; Esen, Sevda; Gerick, David; Gersabeck, Evelina; et al. (The European physical journal. C, Particles and fields, 2016)
A search is presented for massive long-lived particles, in the 20–60 GeV/c2 mass range with lifetimes between 5 and 100 ps. The dataset used corresponds to 0.62 fb −1 of proton-proton collision data collected by the LHCb detector at s√=7TeV. The particles are assumed to be pair-produced by the decay of a Higgs-like boson with mass between 80 and 140 GeV/c2. No excess above the background expectation is observed and limits are set on the production cross-section as a function of the long-lived particle mass and lifetime and of the Higgs-like boson mass.